Dakwah melalui Distribusi Zakat dan Dampaknya pada Implementasi Keagamaan Muallaf di Indonesia: Da’wah Through Zakat Distribution and Its Impact on the Muallaf Religious Implementation In Indonesia - choirin, muhammad; Kurniawan, Rizaludin; Saputra Arbi, Dion; A'toa' Bin Mokhtar, Ahmad (Jurnal Bimas Islam, 2023)
This study explores the level of Islamic practice for Muallaf assisted by the Zakat Management Institute (LPZ) in Indonesia, which receive zakat funds. In addition, this study will also analyse the relationship between the level of zakat distribution and the level of religious practice, with the main focus on using the allocation of zakat funds to strengthen faith and practice Islamic values. This study uses quantitative methods involving as many as 135 converts as respondents. The descriptive statistical method describes the impact of zakat distributed by LPZ to asnaf Muallaf as zakat recipients. The results of this study indicate that the level of distribution of zakat and religious practice is positively related and shows high coefficient values of 4.45 and 4.63. Then, if viewed based on the correlation between the distribution of zakat and spiritual preparation for converts, it is significantly high. Therefore, the Zakat Management Institute (LPZ) can optimise the empowerment of zakat for converts.